High-thermal-conductivity sulfide solid-state electrolyte and preparation method and application thereof

CN116231052BActive Publication Date: 2026-11-03SHENZHEN GUYAN NEW MATERIAL TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211710216.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-29
Publication Date
2026-11-03
Estimated Expiration
2042-12-29

AI Technical Summary

Technical Problem

Existing sulfide solid electrolytes have poor thermal conductivity, resulting in poor fast charging performance and rapid recovery performance at low temperatures in all-solid-state batteries.

Method used

A high thermal conductivity sulfide solid electrolyte is prepared by doping a ceramic thermally conductive material into an initial sulfide solid electrolyte, mixing it by ball milling, and then heating it to 300-550℃ in a tube furnace for 1-20 hours with inert gas.

Benefits of technology

The thermal conductivity of the sulfide solid electrolyte is improved, allowing it to recover to a high ionic conductivity state more quickly at low temperatures, thereby enhancing the fast charging capability of the all-solid-state battery and its ability to quickly recover to normal/high temperature performance at low temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116231052B_ABST
    Figure CN116231052B_ABST
Patent Text Reader

Abstract

The application discloses a high-thermal-conductivity sulfide solid electrolyte and a preparation method and application thereof, and relates to the technical field of solid electrolyte materials. The preparation method comprises the following steps: uniformly mixing an initial sulfide solid electrolyte and a ceramic thermal conductive material by ball milling to obtain a mixture; and placing the mixture in a tube furnace, passing inert gas to heat the mixture to 300-550 DEG C, and reacting for 1-20 h to obtain the high-thermal-conductivity sulfide solid electrolyte. After the ceramic thermal conductive material is doped in the initial sulfide solid electrolyte, the sulfide solid electrolyte can be quickly recovered from a low-temperature low-ionic-conductivity state to a high-ionic-conductivity state. A full solid-state battery using the high-thermal-conductivity sulfide solid electrolyte can be quickly heated to a high temperature after an external heating system is started. Therefore, the high-thermal-conductivity sulfide solid electrolyte prepared by the application can improve the fast charging and low-temperature fast recovery performance of the full solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of solid electrolyte technology, and in particular to a high thermal conductivity sulfide solid electrolyte, its preparation method, and its application. Background Technology

[0002] With the rapid development of portable mobile devices and new energy vehicles, and the future construction of energy storage systems, there is a growing need for more efficient energy storage devices to meet the ever-increasing demand. Currently, lithium-ion batteries, with their advantages of high energy density, high operating voltage, and long cycle life, have become the mainstay of energy storage devices. However, commercially available lithium-ion batteries use ester or ether organic compounds as electrolyte solvents. These organic compounds are prone to side reactions with electrode materials during battery electrochemical cycling, producing gas and posing a fire hazard. Compared to lithium-ion batteries made with liquid electrolytes, solid-state electrolytes have advantages such as non-volatile, non-flammable, non-corrosive, and high mechanical strength. All-solid-state batteries made with solid-state electrolytes have extremely high safety.

[0003] Currently, there are three main types of solid electrolytes: polymer solid electrolytes, oxide solid electrolytes, and sulfide solid electrolytes. Among them, polymer solid electrolytes have good film-forming properties, but low lithium-ion conductivity; oxide solid electrolytes are not sensitive to water and oxygen and have moderate conductivity, but poor interfacial contact with electrode materials; sulfide solid electrolytes have ionic conductivity comparable to liquid electrolytes, an ion transference number close to 1, and good wettability with electrode materials, making them the most promising direction for all-solid-state batteries.

[0004] Because all-solid-state batteries use solid electrolytes, and there is no solvent flowing within solid electrolytes, lithium-ion transport within them is accomplished through ion migration. The lithium-ion transport capability of solid electrolytes is greatly affected by temperature. Therefore, whether used in fast charging or low-temperature environments, all-solid-state batteries require the ability to rapidly heat up to the ideal temperature. However, the thermal conductivity of solid electrolyte powder itself is very limited, restricting the future commercial use of all-solid-state batteries.

[0005] Therefore, existing technologies still need to be improved and developed. Summary of the Invention

[0006] In view of the shortcomings of the prior art, the purpose of this invention is to provide a high thermal conductivity sulfide solid electrolyte, its preparation method and application, in order to solve the problem that the poor thermal conductivity of existing sulfide solid electrolytes leads to poor fast charging and low-temperature rapid recovery performance of all-solid-state batteries.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a high thermal conductivity sulfide solid electrolyte, comprising the steps of:

[0009] The initial sulfide solid electrolyte and the ceramic thermally conductive material were ball-milled and mixed to obtain a mixture.

[0010] The mixture is placed in a tube furnace, inert gas is introduced, and the temperature is raised to 300-550°C for 1-20 hours to obtain the high thermal conductivity sulfide solid electrolyte.

[0011] The method for preparing the high thermal conductivity sulfide solid electrolyte, wherein the initial sulfide solid electrolyte is one of LPSC, LGPS, and LPS, wherein the chemical formula of LPSC is Li 6-x PS 5-x Cl 1+x , 0≤x≤0.8; the chemical formula of LGPS is Li 11-y M 2-y P 1+y S 12 M = one of Ge and Si, 0.5≤y≤1.5; the chemical formula of LPS is 75Li2S-25P2S5.

[0012] The method for preparing the high thermal conductivity sulfide solid electrolyte, wherein the ceramic thermally conductive material is one or more of beryllium oxide, aluminum oxide, aluminum nitride, silicon carbide, and silicon nitride.

[0013] In the preparation method of the high thermal conductivity sulfide solid electrolyte, the molar ratio of ceramic thermally conductive material in the mixture is 1-50%.

[0014] In the method for preparing the high thermal conductivity sulfide solid electrolyte, the inert gas is one or more of argon, helium, neon, and nitrogen.

[0015] In the method for preparing the high thermal conductivity sulfide solid electrolyte, the flow rate of the inert gas is 0.05-1 L / min.

[0016] The method for preparing the high thermal conductivity sulfide solid electrolyte includes a step in which the mixture is placed in a tube furnace and heated to 300-550°C for 1-20 hours with an inert gas atmosphere, and the heating rate is 1-5°C / min.

[0017] The method for preparing the high thermal conductivity sulfide solid electrolyte further includes the following steps: after placing the mixture in a tube furnace and heating it to 300-550°C for 1-20 hours by passing an inert gas through it, the mixture is further cooled to room temperature at a rate of 1-5°C / min.

[0018] A high thermal conductivity sulfide solid electrolyte, wherein it is prepared by the preparation method of the high thermal conductivity sulfide solid electrolyte described in this invention.

[0019] A high thermal conductivity sulfide solid electrolyte, wherein the high thermal conductivity sulfide solid electrolyte of the present invention is used to prepare an all-solid-state battery.

[0020] Beneficial Effects: By doping the initial sulfide solid electrolyte with ceramic thermally conductive materials, this invention enables the sulfide solid electrolyte to recover from its low ionic conductivity state at low temperatures to a high ionic conductivity state more quickly. All-solid-state batteries using the high thermal conductivity sulfide solid electrolyte of this invention can be heated to a high-performance state more quickly after the external heating system is activated. Therefore, the high thermal conductivity sulfide solid electrolyte prepared by this invention can improve the fast charging capability and the ability of all-solid-state batteries to quickly recover from low temperatures to normal / high-temperature performance. Attached Figure Description

[0021] Figure 1 This is a flowchart of a method for preparing a high thermal conductivity sulfide solid electrolyte according to the present invention. Detailed Implementation

[0022] This invention provides a high thermal conductivity sulfide solid electrolyte, its preparation method, and its application. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the invention is further described in detail below. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.

[0023] Please see Figure 1 , Figure 1 A flowchart of a method for preparing a high thermal conductivity sulfide solid electrolyte provided by the present invention is shown in the figure, which includes the following steps:

[0024] S10. The initial sulfide solid electrolyte and the ceramic thermally conductive material are ball-milled and mixed to obtain a mixture.

[0025] S20. The mixture is placed in a tube furnace and heated to 300-550°C with inert gas for 1-20 hours to obtain the high thermal conductivity sulfide solid electrolyte.

[0026] Specifically, due to the low-temperature performance issues of all-solid-state batteries and the requirement for fast charging, it is necessary to rapidly heat the entire all-solid-state battery to the ideal temperature. However, the usual method of adding external thermally conductive materials cannot solve the problem of the poor thermal conductivity of the solid electrolyte powder itself, resulting in the internal and external temperatures not reaching the required values ​​quickly during the heating process. Therefore, this invention starts from the source, namely the solid electrolyte powder with poor thermal conductivity, by doping the initial sulfide solid electrolyte with ceramic thermally conductive materials. This allows the sulfide solid electrolyte to recover from its low ionic conductivity state at low temperatures to a high ionic conductivity state more quickly. All-solid-state batteries using the high thermal conductivity sulfide solid electrolyte of this invention can be heated to a high-temperature, high-performance state more quickly after the external heating system is activated. Therefore, the high thermal conductivity sulfide solid electrolyte prepared by this invention can improve the fast charging capability and the ability of all-solid-state batteries to quickly recover from low temperatures to normal / high-temperature performance.

[0027] In some embodiments, the initial sulfide solid electrolyte is one of LPSC, LGPS, and LPS, wherein LPSC has the chemical formula Li 6-x PS 5-x Cl 1+x , 0≤x≤0.8; the chemical formula of LGPS is Li 11-y M 2-y P 1+y S 12 M = one of Ge and Si, 0.5≤y≤1.5; the chemical formula of LPS is 75Li2S-25P2S5.

[0028] In some embodiments, the ceramic thermally conductive material is one or more of beryllium oxide, aluminum oxide, aluminum nitride, silicon carbide, and silicon nitride, but is not limited thereto.

[0029] In some embodiments, the initial sulfide solid electrolyte and the ceramic thermally conductive material are ball-milled and mixed to obtain a mixture, wherein the molar ratio of the ceramic thermally conductive material is 1-50%. In this embodiment, although the ceramic thermally conductive material is an electron-ion insulator, when a certain amount of the ceramic thermally conductive material is added (molar ratio of 1-50%), it only covers a portion of the outer surface layer of the initial sulfide solid electrolyte in the form of dots, and does not completely encapsulate it. Therefore, the high thermal conductivity sulfide solid electrolyte finally obtained can ensure the improvement of thermal conductivity while ensuring that the ionic conductivity does not drop sharply.

[0030] In some embodiments, the step of placing the mixture in a tube furnace and heating it to 300-550°C for 1-20 hours with an inert gas is described, with a heating rate of 1-5°C / min. The inert gas is one or more of argon, helium, neon, and nitrogen, and the flow rate of the inert gas is 0.05-1 L / min.

[0031] In some embodiments, after placing the mixture in a tube furnace and heating it to 300-550°C for 1-20 hours by passing an inert gas through it, the process further includes the step of cooling it to room temperature at a rate of 1-5°C / min.

[0032] In some embodiments, a high thermal conductivity sulfide solid electrolyte is also provided, which is prepared by the preparation method of the high thermal conductivity sulfide solid electrolyte described in this invention.

[0033] In some embodiments, a high thermal conductivity sulfide solid electrolyte is also provided, wherein the high thermal conductivity sulfide solid electrolyte of the present invention is used to prepare an all-solid-state battery. The present invention starts from the source, namely the solid electrolyte powder with poor thermal conductivity, and by doping the initial sulfide solid electrolyte with ceramic thermally conductive materials, the sulfide solid electrolyte can recover from a low ionic conductivity state at low temperatures to a high ionic conductivity state more quickly. All-solid-state batteries using the high thermal conductivity sulfide solid electrolyte of the present invention can be heated to a high ionic conductivity state more quickly after the external heating system is activated. Therefore, the high thermal conductivity sulfide solid electrolyte prepared by the present invention can improve the fast charging capability and the ability of all-solid-state batteries to quickly recover from low temperatures to normal / high temperature performance.

[0034] The present invention will be further explained and illustrated below through specific embodiments:

[0035] Example 1

[0036] Select Li 6-x PS 5-x Cl 1+x As the initial electrolyte, x is set to 0, the total mass is 11.26g, BeO is selected as the ceramic thermal conductive material, the molar ratio a% is set to 1%, the sintering temperature is 550℃, the heating rate is 3℃ / min, the holding time is 24h, the gas introduced is argon, and the gas flow rate is 1L / min, resulting in Li6PS5Cl(BeO). 0.01 The powder.

[0037] Example 2

[0038] Select Li 6-x PS 5-x Cl 1+x As the initial electrolyte, x was set to 0.1, the total mass was 13.68 g, Al₂O₃ was selected as the ceramic thermal conductive material, the molar ratio a% was set to 5%, the sintering temperature was 540℃, the heating rate was 1℃ / min, the holding time was 20 h, and argon gas was introduced at a flow rate of 0.5 L / min, resulting in Li 5.9 PS 4.9 Cl 1.1 (Al2O3) 0.05 The powder.

[0039] Example 3

[0040] Select Li 6-x PS 5-x Cl 1+x As the initial electrolyte, x was set to 0.3, the total mass was 13.84 g, Al₂O₃ was selected as the ceramic thermal conductive material, the molar ratio a% was set to 10%, the sintering temperature was 550℃, the heating rate was 5℃ / min, the holding time was 24 h, and argon gas was introduced at a flow rate of 0.5 L / min, resulting in Li 5.7 PS 4.7 Cl 1.3 (Al2O3) 0.1 The powder.

[0041] Example 4

[0042] Select Li 6-x PS 5-x Cl 1+x As the initial electrolyte, x was set to 0.5, the total mass was 14.63 g, Al₂O₃ was selected as the ceramic thermal conductive material, the molar ratio a% was set to 20%, the sintering temperature was 540℃, the heating rate was 3℃ / min, the holding time was 30 h, and argon gas was introduced at a flow rate of 0.5 L / min, resulting in Li 5.5 PS 4.5 Cl 1.5 (Al2O3) 0.2 The powder.

[0043] Example 5

[0044] Select Li 6-x PS 5-x Cl 1+x As the initial electrolyte, x was set to 0.6, the total mass was 13.71 g, AlN was selected as the ceramic thermal conductive material, the molar ratio a% was set to 50%, the sintering temperature was 540℃, the heating rate was 2℃ / min, the holding time was 24 h, and argon gas was introduced at a flow rate of 0.8 L / min, resulting in Li 5.4 PS 4.4 Cl 1.6 (AlN) 0.5 The powder.

[0045] Example 6

[0046] Select Li 6-x PS 5-x Cl 1+xAs the initial electrolyte, x was set to 0.8, the total mass was 16.12 g, AlN was selected as the ceramic thermal conductive material, the molar ratio a% was set to 25%, the sintering temperature was 530℃, the heating rate was 2℃ / min, the holding time was 30 h, and argon gas was introduced at a flow rate of 0.8 L / min to obtain Li 5.2 PS 4.2 Cl 1.8 (AlN) 0.25 The powder.

[0047] Example 7

[0048] Select Li 11-y M 2-y P 1+y S 12 As the initial electrolyte, Ge was selected as M, y was set to 0.5, and the total mass was 20.47 g. SiC was selected as the ceramic thermal conductive material, with a molar doping ratio of 15% (a%). The sintering temperature was 540℃, the heating rate was 3℃ / min, the holding time was 18 h, and argon gas was introduced at a flow rate of 0.3 L / min. Li was then obtained. 10.5 Ge 1.5 P 1.5 S 12 (SiC) 0.15 The powder.

[0049] Example 8

[0050] Select Li 11-y M 2-y P 1+y S 12 As the initial electrolyte, Ge was selected as M, y was set to 1, and the total mass was 21.69 g. SiC was selected as the ceramic thermal conductive material, with a molar doping ratio of 20% (a%). The sintering temperature was 550℃, the heating rate was 3℃ / min, the holding time was 24 h, and argon gas was introduced at a flow rate of 0.3 L / min. Li was then obtained. 10 GeP2S 12 (SiC) 0.25 The powder.

[0051] Example 9

[0052] Select Li 11-y M 2-y P 1+y S 12 As the initial electrolyte, M was chosen as Si, y was set to 1.5, and the total mass was 19.48 g. The ceramic thermally conductive material was Si3N4 with a doping molar ratio of a% of 10%. The sintering temperature was 520℃, the heating rate was 3℃ / min, the holding time was 20 h, and argon gas was introduced at a flow rate of 0.5 L / min. This yielded Li. 9.5Si 0.5 P 2.5 S 12 (Si3N4) 0.1 The powder.

[0053] Example 10

[0054] 75Li₂S-25P₂S₅ was selected as the initial electrolyte, with a total mass of 10.51 g. Si₃N₄ was chosen as the ceramic thermal conductive material, with a molar doping ratio a% of 15%. The sintering temperature was 400℃, the heating rate was 1℃ / min, the holding time was 16 h, and argon gas was introduced at a flow rate of 1 L / min to obtain Li₃PS₄(Si₃N₄). 0.15 The powder.

[0055] Comparative Example 1

[0056] Except for the absence of BeO, it is identical to Example 1.

[0057] Comparative Example 2

[0058] Except for the absence of SiC, it is identical to Example 7.

[0059] Comparative Example 3

[0060] Except for the absence of Si3N4, it is identical to Example 10.

[0061] Test case

[0062] 1. Ionic conductivity test: In an argon glove box, 0.2g of the solid electrolyte powder from Examples 1-10 and Comparative Examples 1-3 was poured into an alumina sleeve with a diameter of 10mm. The powder was then compressed into a tablet using a tablet press at a pressure of 300MPa for 1 minute. The thickness of the solid electrolyte disc was measured using a micrometer. A piece of carbon-coated copper foil (carbon end facing the solid electrolyte) was placed at each end of the solid electrolyte disc as a blocking electrode. The disc was then placed in a conductivity test kit, pressurized to 300MPa, and connected to an electrochemical workstation for EIS testing.

[0063] 2. EIS test: Apply an AC voltage of 50mV and test using the AC impedance method in the frequency range of 1MHz to 1Hz. The test results are shown in Table 1.

[0064] Table 1. Conductivity Test Results

[0065]

[0066]

[0067] As can be seen from the results in Table 1, the addition of ceramic thermal conductive materials will have a certain impact on the original ionic conductivity of the initial sulfide solid electrolyte.

[0068] Low-temperature conductivity recovery performance test: After the samples in Table 1 that have been tested at room temperature are completed, the tested mold batteries are packaged and then moved into a constant temperature and humidity chamber. After connecting to the electrochemical workstation, the constant temperature and humidity chamber is set to -30℃. After the constant temperature and humidity chamber reaches -30℃, it is left for 4 hours to ensure that the powder has reached temperature stability in the constant temperature and humidity chamber. After testing the impedance at low temperature once, the door of the constant temperature and humidity chamber is closed and the packaged mold is moved to room temperature. The electrochemical impedance spectrum is tested every 10 minutes and the corresponding ionic conductivity is calculated. The results are shown in Table 2.

[0069] Table 2 Test Results

[0070]

[0071]

[0072] As shown in Table 2, the addition of ceramic thermally conductive material allows the sulfide solid electrolyte to recover from its low ionic conductivity at low temperatures to high ionic conductivity more quickly. The all-solid-state battery using the solid electrolyte of this invention can be heated to a high temperature more rapidly after the external heating system is activated. Therefore, the solid electrolyte of this invention can improve the fast charging capability and the ability of all-solid-state batteries to quickly recover from low temperatures to normal / high temperature performance.

[0073] It should be understood that the application of the present invention is not limited to the examples above. Those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims.

Claims

1. A method for preparing a high thermal conductivity sulfide solid electrolyte, characterized in that, Including the following steps: The initial sulfide solid electrolyte and the ceramic thermally conductive material were ball-milled and mixed to obtain a mixture. The ceramic thermally conductive material is one or more of beryllium oxide, aluminum oxide, aluminum nitride, silicon carbide, and silicon nitride, and the molar ratio of the ceramic thermally conductive material is 1-50%. The mixture is placed in a tube furnace and inert gas is introduced. The temperature is increased to 300-550°C at a heating rate of 1-5°C / min and reacted for 1-20 hours to obtain the high thermal conductivity sulfide solid electrolyte. The ceramic thermally conductive material is applied in a dotted manner to a portion of the outer surface layer of the initial sulfide solid electrolyte, without constituting complete coverage.

2. The method for preparing the high thermal conductivity sulfide solid electrolyte according to claim 1, characterized in that, The initial sulfide solid electrolyte is one of LPSC, LGPS, and LPS, wherein the chemical formula of LPSC is Li. 6-x PS 5-x Cl 1+x , 0≤x≤0.8; the chemical formula of LGPS is Li 11-y M 2-y P 1+y S 12 M = one of Ge and Si, 0.5≤y≤1.5; the chemical formula of LPS is 75Li2S-25P2S5.

3. The method for preparing the high thermal conductivity sulfide solid electrolyte according to claim 1, characterized in that, The inert gas is one or more of argon, helium, neon, and nitrogen.

4. The method for preparing the high thermal conductivity sulfide solid electrolyte according to claim 1, characterized in that, The flow rate of the inert gas is 0.05-1 L / min.

5. The method for preparing the high thermal conductivity sulfide solid electrolyte according to claim 1, characterized in that, After placing the mixture in a tube furnace and heating it to 300-550°C for 1-20 hours by passing an inert gas through it, the process further includes the step of cooling it to room temperature at a rate of 1-5°C / min.

6. A high thermal conductivity sulfide solid electrolyte, characterized in that, It is prepared by the preparation method of the high thermal conductivity sulfide solid electrolyte according to any one of claims 1-5.

7. An application of a high thermal conductivity sulfide solid electrolyte, characterized in that, The high thermal conductivity sulfide solid electrolyte described in claim 6 is used to prepare an all-solid-state battery.

Citation Information

Patent Citations

  • A composite solid electrolyte separator, a preparation method thereof and a lithium ion battery

    CN109244547A

  • Composite solid-state electrolyte membrane, preparation method thereof and solid-state battery

    CN113314764A